The broad antibacterial activity of a small synthetic receptor for cellular phosphatidylglycerol lipids - Alsuri, Maruthi Ram; Bower, Benjamin D; Burns, Dennis H; Fraire, Guadalupe; Seelam, Bhusi R; Shaban, Rima; Shaban, Sara; Schneegurt, Mark A (Folia microbiologica, 2023)
A small receptor molecule composed of a porphyrin core with tetrakis-ammonium glycine pickets (liptin 3e) appears to target anionic phosphatidylglycerol (PG) lipid head groups through multifunctional binding-pocket complementarity. Although a major component of bacterial cell membranes, PG is not widely found in animal cells, making PG potentially selective for bacterial targeting. Growth of microbial isolates was monitored in liquid cultures treated with liptin 3e by dilution plate counts and turbidity. Inhibition of growth by liptin 3e was observed for the ESKAPE human pathogens (Enterobacter aerogenes, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterococcus faecium), Escherichia coli, Mycobacterium smegmatis, Streptococcus sobrinus, and methicillin-resistant S. aureus (MRSA), with certain species suppressed at <1 μg/mL (sub-μM) concentrations. Prolonged lag phases were observed, although cell viability was mainly unaffected, suggesting that liptin treatment caused bacteriostasis. Cultures treated with liptin 3e eventually recovered, resumed growth, and reached the same final densities as untreated cultures. Growth of the fungus Candida albicans was not appreciably inhibited by liptin 3e. If liptins exhibit bacteriostasis through broad extracellular binding to PG head groups, thereby disrupting cellular processes, liptins may be considered for development into preclinical drug candidates or be useful as a targeting system for molecular beacons or antibacterial drugs.
Keywords: Microbial Sensitivity Tests; methicilin rezistentní Staphylococcus aureus; antibakteriální látky; Enterococcus faecium; lidé; receptory umělé; fosfatidylglyceroly; Escherichia coli; Animals; Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; zvířata; Humans; mikrobiální testy citlivosti; Phosphatidylglycerols; Receptors, Artificial